Quantitative relationships between leaf blast and neck blast and their effect on grain filling and grain weight in upland rice - Prabhu, Anne Sitarama; Faria, Josias Corrêa de (Pesquisa Agropecuaria Brasileira, 2014)
A quadratic relationship between leaf blast (Pyricularia oryzae Cav.) at boot stage and the percentage of panicles affected with neck blast at the dough stage was obtained. The incidence of neck blast was not directly proportional to increase in inoculum produced by leaf lesions. The relationship between leaf blast at the maximum tillering phase and the dry weight of grain expressed as a percentage dry weight of grain at maturity revealed that the dry matter increased logarithmically in both high and negligible levels of leaf blast intensities. Grain development did not stop even at high leaf blast intensity at the tillering phase. The relationship between grain weight and time of neck infection was exponential. While the loss in 1.000 grain weight was 38% when panicles were infected at the milk stage, it decreased to 5% at the mature stage of grain development. The loss in grain weight/panicle increased with increase in neck blast.